Managing Land Assets For Sustainable Goals To Generate Income Of University - Wardhana, Mahendra; Kautsar, Achmad; Fithroni, Hijrin; Liana, Corry; Bhilawa, Loggar (International Journal of Educational Research & Social Sciences, 2023)
This research aims to find out that increasing university income from land development is a complicated process that requires knowledge and skills in various aspects such as law, urban planning, and the civil structure of buildings that will stand on the land. This research will adopt a descriptive qualitative research approach to understand a particular phenomenon. This approach allows researchers to collect descriptive data to answer research questions regarding optimizing university land management. The research subjects in this study were 30 people consisting of leaders of Surabaya State University and stakeholders who were partners and involved in land development in the University area. Research findings show that sustainable land development is a goal that the University wishes to achieve in the short and long term and needs to be supported by strong financial resources. These results have significant implications for other universities that are managing land assets to contribute income to sustainable land development.